Experimental infection of dogs with Echinococcus granulosus (Batsch, 1986) from protoscoleces of donkey’s hydatid cyst - Rahif, Raad Harbi; Atae, Amal Hassan (The Iraqi Journal of Veterinary Medicine, 2004)
This study was conducted, for the 1st time in Iraq, to infect 5 puppies, 1 - 5 month old, with protoscoleces of hydatid cyst isolated from the liver of donkey, slaughtered at zoo abattoir of Al-Zawra park in Baghdad, at a dose rate of 10000 protoscoieces i puppy (n=2) and 20000 protoscoleces / puppy (n=3) for 35 and 40 days post infection. The dogs were killed and the developed Echinococcus granulosus were isolated from the small intestine. Results of the study revealed variation in the period of maturation of the collected cestodes, and the mean total length of the mature worms at 35 days PI was 4.53+ 0.24 mm, and for those at 40 days PI was 7+ 0.20 mm, whereas for the gravid ones at the same age of the latter was 8.57 + 0.25 mm. Results found that infection rate with E. granulosus, which their strobilae composed from 4 proglottids at 35 days PI, was 29.03%, and with those, which their strobilae composed from 5 proglottids at 40 days PI, the rate was 0.76%. It was found that the mean length of the gravid proglottid equal to or longer than half the total worm length with a ratio of 1.77 + 0.05 for those at 35 days of age, and 2.2 + 0.35 and 1.93 + 0.01 for mature and gravid cestodes at the age of 40 days.